Cross-cultural adaptation and psychometric properties of the Thai version of the Patient-Reported Outcomes Measurement Information System Short Form-Depression 8a in individuals with chronic low back pain - Ruetaichanok Sansatan (Chulalongkorn University, 2023)
117 pages